Homo investor : um ensaio sobre a concepção de racionalidade dos agentes em teorias de investimento - Marks, Larisse (Universidade do Vale do Rio dos Sinos, 2017)
Given the importance of investment for growth of the Economy and it’s continuing presence in the lives of economic agents, several theoretical conceptions are dedicated to the understanding of decision-making. However, there is no agreement on the explanations of the investment models and the real decision-making process, just as there is no agreement in the postulate of rationality too. The purpose of this study is to identify which perceptions of rationality support the investment theories of Fisher, Keynes, theories derived from Keynes (Post-Keynesian, Neo Keynesian and New Keynesian), Kalecki and Behavioral Finance, through a dialectical discussion about the understanding of investment throughout economic history, by assessing exclusively the contents pertinent to rationality. One of the main results of this study is that theories that reject the conception of a completely rational being do not adopt the idea of a totally irrational individual; their disagreement is relative to the degree of rationality employed in the models.
Keywords: Racionalidade; Teoria de Investimento; Finanças Comportamentais; Rationality; Investment theory; Behavioral finance; ACCNPQ::Ciências Sociais Aplicadas::Economia